(untitled) (Foro de Educacion, 2026)
The improvement of teachers’ work engagement and creativity, as well as the overall development of schools and the enhancement of teachers’ overall quality, all depend on a high-performing teaching workforce. This study aims to explore the impact of perceived school organizational climate on the work performance of primary school teachers in Shandong Province, China, and verify the mediating role of professional commitment. The gender, educational background, and teaching experience of teachers were included as background variables in the study. A convenience sampling method was employed to collect questionnaire data from 380 teachers across 12 elementary schools in Shandong Province, China. Findings reveal significant gender differences in perceived organizational climate, while no significant gender differences exist in work performance or career commitment. Teachers with different teaching experiences and educational backgrounds showed significant differences in perceived school organizational climate, work performance, and professional commitment. Perceived school organizational climate had a significant positive impact on work performance. Professional commitment had a significant positive impact on work performance. Professional commitment mediates the relationship between perceived organizational climate and work performance. This study empirically examines the mediating effect of professional commitment in the relationship between perceived school organisational climate and work performance, highlighting the crucial role of professional commitment in teachers’ work environments and providing new empirical evidence to support the application of related theories.